Pengaruh Lingkungan Kerja Non Fisik dan Motivasi Kerja Terhadap Semangat Kerja Pada Dinas Kesehatan Kabupaten Bima - Redito Dirham; Ita Purnama (Journal of Creative Student Research, 2023)
AbstractThis research aims to determine the influence of the non-physical work environment and work motivation on work enthusiasm at the Bima District Health Service. In this research, the type of Associative research is used, namely research that is to find out the relationship between two or more variables and in this research the researcher wants to know the relationship between the non-work environment influence variables (X1), work motivation (X2), and the work enthusiasm variable (Y). The population used in the research was 84 civil servants who were at the Bima District Health Service. The sampling technique in this research was using the Purposive Sampling technique. The sampling in this research was 84 respondents. The research instrument uses a Likert scale using validity tests, reliability tests, classical assumption tests, multiple linear regression, correlation coefficient analysis (R), determination coefficient analysis (R2), t test and f test. The results of the research show that 1) There is a significant influence of the Non-Physical Work Environment on Work Spirit in Bima District Health Service employees. 2) There is no significant influence of Work Motivation on Work Morale among employees of the Bima District Health Service. 3) Non-Physical Work Environment and Work Motivation together have a significant effect on Work Morale among employees of the Bima District Health Service.